2011
DOI: 10.1002/jbm.a.33248
|View full text |Cite
|
Sign up to set email alerts
|

Repair of articular cartilage defects with a novel injectablein situforming material in a canine model

Abstract: We developed an ultra-purified in situ forming gel as an injectable delivery vehicle of bone marrow stromal cells (BMSCs). Our objective was to assess reparative tissues treated with autologous BMSCs implanted using the injectable implantation system into osteochondral defects in a canine model. Forty-eight osteochondral defects in the patella groove of the knee joint were created in 12 adult beagle dogs (two defects in each knee). The defects were divided into a defect group (n = 16), an acellular novel mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 48 publications
2
29
0
Order By: Relevance
“…There was much variation in the number of cells implanted and the number of cell passages from 3–10 or more [79, 86]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was much variation in the number of cells implanted and the number of cell passages from 3–10 or more [79, 86]. …”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies [49, 65, 72, 75, 81, 86, 89–97] used a mixture of solutions prepared from hyaluronic acid [65, 92, 94–97], phosphate buffer solution [91], plasma [75], basal medium with chondrogenesis [89], collagen acid [93], sodium alginate [86] or a growth factor medium [90]. Two studies used MSCs only [49, 72].…”
Section: Resultsmentioning
confidence: 99%
“…An alternative study by Igarashi et al, conducted without growth factors, treated osteochondral defects in a canine model. 61 Their approach consisted of an in situ forming gel based on ultra-purified alginate containing autologous BMSCs. After 16 weeks of recovery, analysis of the treated area was reported as being smooth, firm, and glossy-white.…”
Section: Adult Stem Cell Sourcesmentioning
confidence: 99%
“…The previous study has demonstrated that the ultrapurified alginate gel (UPAL gel) has favorable biological effects on in vitro proliferation and chondrogenesis of bone marrow stromal cells (BMSCs) [26]. In addition, the previous in vivo studies using rabbits and canines have shown that implantation of autologous BMSCs using the UPAL gel enhanced cartilage repair in cartilaginous lesions [26, 27]. Furthermore, the results obtained from these studies indicate that the acellular UPAL gel implantation technique has the potential to repair osteochondral defects by effectively recruiting host BMSCs.…”
Section: Strategic Scaffold Designs Based On Approach For Cartilage Rmentioning
confidence: 99%